Male friendship, homosociality, and women in the Hebrew Bible malignant fraternities - Thiede, Barbara (London New York, NY Routledge, 2022)
Introduction. Honesty, transparency, and sight: some introduction -- Chapter 1. Genesis 38: "Lest we become a laughingstock" -- Chapter 2. David, Jonathan, and Saul: being good at being a man -- Chapter 3. 2 Samuel 13: rape in the royal house -- Chapter 4. Genesis 12, 20, and 26: Bromance in the Bible -- Chapter 5. Judges 19-21: The warrior God and his Levite soldier -- Chapter 6. Judges 4 & 5: Always mothers, never friends -- Conclusion. Toxic for women: conclusions on biblical hegemonic masculinity.
"Male alliances, partnerships, and friendships are fundamental to the Hebrew Bible. This book offers a detailed and explicit exploration of the ways in which shared sexual use of women and women's bodies engenders, sustains, and nourishes such relationships in the Hebrew Bible. Hebrew Bible narratives demonstrate that women and women's bodies are not merely used to foster and cultivate male homosociality, male friendship, and toxic hegemonic masculinity, but rather to engender it and make it possible in the first place. Thiede argues that homosocial bonds between divine and mortal males are part of a continual competition for power, rank, and honor, and that this competition depends on women's bodies for its expression. In a final chapter, she also explores whether female characters in the Hebrew Bible use male bodies to form friendships and alliances to advance female power, status, and rank. The book concludes by arguing that women are essential to the toxic biblical hegemonic masculinity we find in the Hebrew Bible, but only because their bodies are used to make it possible in the first place. This book is intended for scholars of the Hebrew Bible, as well as advanced undergraduate and graduate students in Religious Studies, Women and Gender Studies, Masculinity Studies, Queer Studies, and like fields. The book can also be read profitably by lay students of biblical literature, seminary students, and clergy"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Male friendship in literature; Women in the Bible; Female friendship in literature; Man-woman relationships in the Bible; Masculinity in the Bible